2018
DOI: 10.1590/1807-3107bor-2018.vol32.0022
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter study of oral health behavior among adult subjects from three South American cities

Abstract: The aims of this study were to describe the self-reported oral hygiene habits, dental visit frequency, and gingival bleeding perception in adult populations from three South American cities, and also to assess the association of these variables with sociodemographic data and with the clinical presence of plaque and gingival inflammation. Five-hundred and fifty adult subjects from each city (Porto Alegre, Brazil; Tucumán, Argentina; Santiago, Chile) received full mouth examinations to determine visible plaque a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
13
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 27 publications
7
13
0
6
Order By: Relevance
“…Our study also found that the loss of teeth is associated with toothbrushing habit. These findings are in line with other studies that reported tooth loss as a result of poor oral hygiene causing caries and periodontal diseases [11][12][13][14]37,38]. Our data showed the increasing 20-year trend in the proportion of men and women brushing teeth at least twice a day.…”
Section: Discussionsupporting
confidence: 93%
“…Our study also found that the loss of teeth is associated with toothbrushing habit. These findings are in line with other studies that reported tooth loss as a result of poor oral hygiene causing caries and periodontal diseases [11][12][13][14]37,38]. Our data showed the increasing 20-year trend in the proportion of men and women brushing teeth at least twice a day.…”
Section: Discussionsupporting
confidence: 93%
“…Although the mechanistic explanation for this association is still under debate, it reinforces that oral health self-assessment might play a role as a proxy variable for other health conditions. Finally, the variable "brushing the teeth more than four times a day" in our findings mirrors a high standard of self-care in Latin America [19]. We speculate that this standard of self-care is also extrapolated to other variables related to general health.…”
Section: Discussionsupporting
confidence: 63%
“…Such data indicated that patients were aware of bleeding after toothbrushing and may seek professional treatment only when they already suffered from generalized gingival inflammation. Among Swedish and South American adults, self-reported bleeding resulted in sensitivity ranging from 0.42 to 0.51 for a threshold of ≥50% of bleeding sites [9,47]. After dichotomizing as less and more than 40% of bleeding sites, the sensitivity for occasional bleeding was 0.88 in a Scottish sample of adult patients [15].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, adults aged 60 to 75 years were less likely to self-perceive the symptoms of gingival disease correctly compared to young people. Studies have shown that older people in general tend to overestimate their own oral health compared to young and middle-aged adults, despite the age-associated decline in health status [47,[50][51][52]. The factors that affect self-reported oral health are somewhat unclear, but it has been suggested that subjective reactions to oral conditions strongly influence self-perceived oral health and that this is likely more pronounced in the younger age groups [52].…”
Section: Discussionmentioning
confidence: 99%